Відображення картини світу у фразеології американського варіанта англійської мови - Савчук, Крістіна Юріївна; Savchuk, K. Yu. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті зроблено спробу сформувати сучасне уявлення про США та американців крізь призму фразеоло-гічного фонду американського варіанта англійської мови, оскільки саме фразеологізми є носіями соціально-культурного досвіду певної нації. Подано цілісний огляд американського суспільства, історії, економіки, політики, засобів масової інформації та культури за допомогою фразеологічного складу мови як головного носія культури, традицій та історії народу. Досліджуючи такий феномен, як фразеологічна картина світу, що є основним носієм культурного досвіду, традицій і звичаїв певної нації, ми намагаємося розкрити розуміння американського життя, характеру та нації вцілому. In the article we are making an attempt to shape the contemporary idea about United States of America and its people with the help of phraseological units of American variant of the English language, as phraseological units are the describers of social and cultural experience of a certain nation.We also try to provide a description of phraseological world view, as we consider it to be the main resource and describer of cultural and historical development of a certain nation, in our case we talk about American nation because the research is done on the basis of American phraseologisms. In the article we present a detailed description of American society, history, economics, politics, mass media and culture with the help of phraseological fund as the main describer of culture, traditions and history of a certain nation. While researching such a phenomenon as phraseological world view picture, being the main describer of cultural experience, traditions and customs of a certain nation, we are trying to provide an understanding of American lifestyle, character and nation in general.
Representationof the World View Picture in the Phraseology of American variant of the English Language
Keywords: картина світу; world view picture; мовна картина світу; language world view picture; концептуальна картина світу; conceptual world view picture